Economies of visibility as a moderator of feminism: 'Never mind Brexit. Who won Legs‐it!'. Issue 8 (14th October 2018) - Mavin, Sharon; Elliott, Carole; Stead, Valerie; Williams, Jannine
Abstract : This article utilizes economies of visibility to interpret how two UK women political leaders' bodies are constructed in the press, online and by audience responses across several media platforms via a multimodal analysis. We contribute politicizing economies of visibility, lying at the intersection of politics of visibility and economies of visibility, as a possible new modality of feminist politics. We suggest this offers a space where feminism can be progressed. Analysis illustrates how economies of visibility moderate feminism and tie women leaders in various ways to their bodies; commodities constantly scrutinized. The study surfaces how media insist upon femininity through appearance from women leaders, serving to moderate power and feminist potential. We consider complexities attached to public consumption of powerful women's constructions, set up in opposition, where sexism is visible and visceral. This simultaneously fortifies moderate feminism and provokes feminism. The insistence on femininity nevertheless disrupts, through an arousal of audible and commanding feminist voices, to reconnect with the political project of women's equality.